Method of investigating structural properties of non-stationary signals in information-measuring systems - Шантир, Діана Сергіївна (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of investigating structural properties of nonstationary broadband signals to obtain measurement data on the technical condition of the surveillance object was considered. The analysis of the main approaches to solving this problem was performed. The principle of structural analysis of the measuring signal was formulated. The generalized statistical model of the broadband measurement signal structure was developed. A method of investigating structural properties of nonstationary signals was proposed. A generalized algorithm for this method was given. An analysis of the effectiveness of the research method was carried out. Applying the proposed method allows to reduce the loss of information about changes and trends in the technical condition of the surveillance object by analyzing the structural components of the measuring signal. The research results allow to reduce measurement errors (by about 1.5-2 times, depending on the problem to be solved); exclude gross and systematic measurement errors and eliminate the influence of operator (subjective) errors; minimize environmental effects; build a flexible structure of the IMS; ensure the stability of the algorithm and implement real-time measurement of nonstationary physical process parameters; significantly increase the technological (reduce the measuring instrument production cycle by approximately 2 times) and economic (reduce the measuring instrument cost by at least 3 times) performance.